PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT ROYCE ENTERPRISE COMPANY - rusmitha, rusmitha; Wasiman (SCIENTIA JOURNAL, 2024)
The industrial sector is expanding annually, intensifying competition and necessitating companies to develop various survival strategies, including enhancing employee performance. Key factors influencing employee performance include motivation, discipline, and job satisfaction. The purpose of this study was to determine the effect of motivation, discipline, and job satisfaction on employee performance at PT Royce Enterprise Company. This research uses quantitative methods. A sample of 130 employees was taken with a non-probability sampling technique. The data collection tool in the study was a questionnaire with a Likert scale. The data analysis technique is descriptive statistical analysis, with data quality tests, classical assumption tests, influence tests, and hypothesis tests. The results showed that the performance of PT Royce Enterprise Company employees was influenced by work motivation, work discipline, and job satisfaction. The results of hypothesis testing (H4) indicate that the significance value of the F-statistic is 0.000, which is less than the alpha value of 0.05. Additionally, the calculated F value of 89.516 exceeds the critical F value of 4.12. Therefore, we can accept H4.